1989
DOI: 10.2190/p2d2-nt9r-7wf3-7bwx
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Attitudes toward Patients among Medical Specialties

Abstract: In a prior study a questionnaire was developed which reliably measured a variety of physicians' attitudes toward patients. In the present study we have used this questionnaire to compare the attitudes of physicians specializing in Internal Medicine, Surgery, Pediatrics and Psychiatry with one another and with a group of medical students. One way analyses of variance yielded highly significant differences (p less than .001) among these groups on the "Nurturant-Empathic" attitudinal dimension, as well as on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…These data are the first from the South‐East Asian region to characterise and demonstrate differences in physician attitudes between medical specialties. Our findings prompt further investigation and confirmation of whether physicians with particular attitudinal traits are attracted to medicine (and particular specialties) (20,21), or whether physician attitudes are acquired through professional experience and training (4–18). In addition, data from this study presents findings from an area which has received little attention in the literature and offers a little more insight into the attitudinal differences between the medical specialties examined here.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…These data are the first from the South‐East Asian region to characterise and demonstrate differences in physician attitudes between medical specialties. Our findings prompt further investigation and confirmation of whether physicians with particular attitudinal traits are attracted to medicine (and particular specialties) (20,21), or whether physician attitudes are acquired through professional experience and training (4–18). In addition, data from this study presents findings from an area which has received little attention in the literature and offers a little more insight into the attitudinal differences between the medical specialties examined here.…”
Section: Resultsmentioning
confidence: 54%
“…Differences in physician attitudes have been accounted for by differences in training unique to individual specialties (3) as well as experience and professional socialisation (8,17,18). However, the reverse may also hold true.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that attitudes affect career choice; others, however, have found only a weak relationship. 16 Even though other studies show similar results regarding ®nal-year students and vocational trainees, 12 there are several limitations to our study. First, only a cross-sectional comparison was made; groups were not followed over a longer period of time.…”
Section: Discussionmentioning
confidence: 73%
“…9 Differences in doctors' attitudes have been explained as a result of a complex learning process. 12 For instance, in general practice, a primary care specialty, many problems cannot be diagnosed neatly and many contain psychological and social elements, thus demanding a comprehensive approach and special attention to the consultation. 13 Because of this, vocational training in general practice devotes up to one-third of its curriculum time to interpersonal skills and attitude development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation